2016
DOI: 10.4172/2168-9857.1000168
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Extracorporeal Shock Wave Lithotripsy versus Ureteroscopy Holmium Laser Lithotripsy in the Management of Ureteral Stones: A Cost-effectiveness Analysis

Abstract: Objective: To determine the better cost-effective treatment strategy for ureteral stones in a health district of Eastern Spain.Methods: A total of 180 patients were treated between June 2012 and December 2013 for ureteral stones using two different strategies (SWL as initial treatment and URS as rescue technique vs URS and laser lithotripsy (up to 2 procedures). We performed an economic evaluation through a cost effectiveness analysis comparing costs and outcome. We performed a differentiating model in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…If SWL presents an advantage over other more invasive techniques in the treatment of urinary lithiasis, it is the possibility of performing it on an outpatient basis and using on-demand analgesia-sedation according to patient tolerance. This practice makes it a most cost-effective technique compared to other modalities [ 19 , 20 ]. Complementary therapies including music distraction seem to have acceptable advantages in terms of lowering analgesia requirements and patient anxiety during SWL [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…If SWL presents an advantage over other more invasive techniques in the treatment of urinary lithiasis, it is the possibility of performing it on an outpatient basis and using on-demand analgesia-sedation according to patient tolerance. This practice makes it a most cost-effective technique compared to other modalities [ 19 , 20 ]. Complementary therapies including music distraction seem to have acceptable advantages in terms of lowering analgesia requirements and patient anxiety during SWL [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite several investigations have showed that URS/ RIRS has better cost-effectiveness profile [6][7][8], in Spanish medical setting SWL seems to be superior in terms of direct and indirect cost [6][7][8][9][10]. However, another factor as patient's quality of life (QOL) has been less evaluated, showing so far a slightly dominance of SWL over URS/RIRS in patient's QOL [6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%